2016
DOI: 10.1016/j.jpsychores.2016.03.218
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health and Standard Risk Factors for Myocardial Infarction: A Cohort Study

Abstract: Outcome measures: Cox regression analysis was used to estimate HRs for the end point of first non-fatal or fatal myocardial infarction. HR were adjusted for age, sex, systolic blood pressure, total cholesterol, smoking, diabetes, body mass index, education, physical activity and self-rated health in the categories very good; pretty good; somewhat good; pretty poor or poor.Results: In the cohort, 2062 persons were diagnosed with fatal or non-fatal myocardial infarction. Poor selfrated health adjusted for sex an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Meta‐analyses of smaller studies have also been consistent in reporting associations between poorer self‐reported health and cardiovascular and all‐cause mortality . In a large Swedish general population cohort, poorer self‐reported health was associated with a higher prevalance of multiple cardiovascular risk factors, and with an increased risk of myocardial infarction during follow‐up over ≈13 years …”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Meta‐analyses of smaller studies have also been consistent in reporting associations between poorer self‐reported health and cardiovascular and all‐cause mortality . In a large Swedish general population cohort, poorer self‐reported health was associated with a higher prevalance of multiple cardiovascular risk factors, and with an increased risk of myocardial infarction during follow‐up over ≈13 years …”
Section: Discussionmentioning
confidence: 71%
“…A number of large studies have evaluated associations between self‐reported health and mortality in general populations . In the UK Biobank cohort, which included nearly 500 000 volunteers and evaluated multiple clinical, biomarker, and genetic risk factors, self‐reported health was the strongest single predictor of all‐cause mortality in men and the third strongest mortality predictor in women after a cancer diagnosis and illness or injury .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-item measures of self-rated health (box 1) are widely used as inexpensive tools that are powerful and consistent independent predictors of health outcomes 10 11. In a prospective cohort of over 75 000 Swedish adults, those with poor self-rated health were twice as likely to suffer from myocardial infarction compared with those with better self-rated health 12. A single-item self-rating of diet quality was positively associated with household availability of dark green vegetables and low-fat milk, and negatively associated with availability of sugary drinks and the frequency of fast-food and food-away-from-home consumption 13.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that SRH is an independent predictor of 6-week mortality in older patients hospitalised for an acute condition (7). Poor SRH is associated with an increased incidence of diabetes (8), myocardial infarction (9) and stroke in patients without this disease in their medical history. Interestingly, poor SRH is not correlated with stroke-related mortality (10).…”
Section: Introductionmentioning
confidence: 99%